Aplikasi Android untuk Menghitung Sistem Pencahayaan dan Sistem Pengkondisian Udara - Prasetia, Vicky; Susanti, Hera; Mardiyana, Mardiyana (Infotekmesin, 2024)
Optimal lighting and air conditioning are factors that support the feasibility and comfort of a room. Lighting and air conditioning requirements refer to the provisions contained in the Indonesian National Standard (SNI). The selection of lamps for lighting, Air Conditioner (AC) and Exhaust Fan for air conditioning needs to be adjusted to the needs of the room so that the device can work optimally and efficient electrical energy. The design of lighting needs and room temperature comfort is still done manually, resulting in inefficiency in the building design process. Therefore, this research aims to build an Android application to calculate indoor lighting and air conditioning needs. This research methodology includes identifying lux value standards, room position, and air exchange standards based on room type. Furthermore, an Android application is created that can calculate the need for lamp brightness and air conditions according to the applicable formula. The calculation results are displayed on an Android application that can be operated via a smart phone. This application was tested in several types of rooms with different conditions. The calculation results on the application are compared with manual calculations and proven to be accurate. This research has successfully created an Android application that can help users to design lighting and air conditioning needs efficiently and effectively.